DATE STONE IN THE RATIONS OF COMMERCIAL LAYING HENS DURING REARING PERIOD - T.Taha, Z.; F.Al-Shahbwany, F.; A.Al-Eaissy, G. (The Iraqi Journal of Veterinary Medicine, 2024)
This work was conducted to study the possibility of feeding date stone meal (DSM) to 280 commercial Hisex Brown Pullets during the rearing Period (6-20) weeks of age. The rates of inclusion were O/T1, 30/T2, 60/T3. Seven treatments with two replicates for each were used. Results showed that Pullets in Tl were significant)y heavier at the end of rearing period than those fed no DSM P < 0.05. While Pullets in T3 were significantly lighter than all treatment P < 0.05. Food consumption differed significantly between treatments only during the age of 14-20 weeks P < 0.05. Whereas, egg production was significantly lower in T3 than in all other treatments. Mortality, on the other hand, was not effected by treatments.